Common variants of OPA1 conferring genetic susceptibility to leprosy in Han Chinese from Southwest China. Issue 2 (November 2015) - Xiang, Yang-Lin; Zhang, Deng-Feng; Wang, Dong; Li, Yu-Ye; Yao, Yong-Gang
Highlights: We observed positive associations between OPA1 variants and leprosy susceptibility. Leprosy risk allele C of rs414237 is correlated with lower OPA1 mRNA expression level. OPA1 expression may be down-regulated in leprosy. OPA1 may have interaction with M. leprae -induced differentially expressed genes. Abstract: Background: Leprosy is an ancient chronic infection caused by Mycobacterium leprae . Onset of leprosy was highly affected by host nutritional condition and energy production, (partially) due to genomic loss and parasitic life style of M. leprae . The optic atrophy 1 ( OPA1 ) gene plays an essential role in mitochondria, which function in cellular energy supply and innate immunity. Objective: To investigate the potential involvement of OPA1 in leprosy. Methods: We analyzed 7 common genetic variants of OPA1 in 1110 Han Chinese subjects with and without leprosy, followed by mRNA expression profiling and protein–protein interaction (PPI) network analysis. Results: We observed positive associations between OPA1 variants rs9838374 ( P genotypic = 0.003) and rs414237 ( P genotypic = 0.002) with lepromatous leprosy. expression quantitative trait loci (eQTL) analysis showed that the leprosy-related risk allele C of rs414237 is correlated with lower OPA1 mRNA expression level. Indeed, we identified a decrease of OPA1 mRNA expression in both with patients and cellular model of leprosy. In addition, the PPI analysis showed that OPA1 protein was actively involved in the interaction network of M. leprae induced differentially expressed genes. Conclusion: Our results indicated that OPA1 variants confer risk of leprosy and may affect OPA1 expression, mitochondrial function and antimicrobial pathways.